An assessment of the enterprise-based training modality in the Philippines: Barriers, incentives, and policy gaps - Ian Nicole A. Generalao; Pauline Joy M. Lorenzo; Chrislyn Joanna F. E\~nate; Frances Camille G. Dumalaog; John Joseph S. Ocbina; Kimberly R. Librero; Aniceto C. Orbeta (Philippine Institute for Development Studies (PIDS), 2024)
Demand-driven technical and vocational education and training (TVET) has been associated with positive economic outcomes for the trainees and the participating firms and enterprises. Despite these potential positive implications, numerous studies consistently show the limited involvement of the private sector in training provision and curriculum development in the Philippines. Thus, this study examines the enterprise-based training (EBT) modality in the country by identifying the barriers to entry of industries in co-developing and offering upskilling programs and by evaluating existing incentive mechanisms. A series of key informant interviews (KIIs) and site visits with various stakeholders are conducted to identify prevailing issues and challenges that firms and industries face. To better contextualize the EBT situation, these are complemented by a desk review of the literature and the policy and legal framework governing EBT and an analysis of recent data. This study uncovers the multidimensional and interconnected issues surrounding the alarmingly dismal contribution of EBT to training provision. This study finds clear evidence that despite the abundance of financial and non-financial incentives, existing mechanisms have not been effective in attracting private actors, including firms/enterprises and technical vocational institutions (TVIs), to implement EBT programs. Other factors include gaps in the definition, scope, and measure of EBT, limited capacity of implementers, unresponsiveness of training programs, and intersectoral and interagency coordination concerns. This study has three main contributions. First, the elaborate discussion of the various EBT programs and the associated incentives can facilitate a better understanding and deeper appreciation of EBT. Second, policymakers can learn from and adopt good practices on industry involvement in TVET highlighted throughout the study. Finally, policy recommendations are formulated and presented to address the identified barriers and disincentives which have persistently discouraged industry involvement in skills development.
Keywords: 330; enterprise-based training; TVET; industry-led; barriers; incentives